Study of hybrid induction heating in distillation process - Hartini, Hamzah (2012)
Contamination of the conventional water resources created several technological problems for industry and domestic water supplies.Apart from that,in order to develop more economical sustainability for researchers,industrial chemical and pharmaceutical processing,so the investigation of hybrid separation processes is proposed.The induction heating concept will be applied because of this technological method will improved the distillation process. Due to this,there are two kinds of method will carried out, which are the induction heating technique and also the traditional heating technique.For the hybrid technique, the heating mantle will be used as the medium of heating element and also used reservoir water as the inlet of the process. The reservoir water will be used optimally without losing single drop of water (prevent wastage).Then,the temperature will be set on 800C(inlet)and constantly at 50Hz.Onward, repeated on 900C, 1000C and 1100C.Similarly for the traditional heating method,equivalent procedure will used but different in heating element technique.Further on,the results of these kinds of methods will be comparing to determine the best results.Therefore,the expected results are;the best quality of distilled water is produced by using induction heating technique and also can reduced the electrical energy consumption.